2007
DOI: 10.1074/jbc.m608106200
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Bioactive Fibroblast Growth Factor-2 into Cubic Proteinous Microcrystals (Bombyx mori Cypovirus Polyhedra) That Are Insoluble in a Physiological Cellular Environment

Abstract: The supramolecular architecture of the extracellular matrix and the disposition of its specific accessory molecules give rise to variable heterotopic signaling cues for single cells. Here we have described the successful occlusion of human fibroblast growth factor-2 (FGF-2) into the cubic inclusion bodies (FGF-2 polyhedra) of the Bombyx mori cytoplasmic polyhedrosis virus (BmCPV). The polyhedra are proteinous cubic crystals of several microns in size that are insoluble in the extracellular milieu. Purified FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 22 publications
(17 reference statements)
0
36
0
Order By: Relevance
“…Collectively, Fgf2 suppressed the osteogenic process in AX cells at the mRNA level and the mechanism might be dependent on the hyperactivation of Erk1/2. To further evaluate the earlier findings in vivo, AX cells were coinjected with Fgf2 or Lif polyhedra which were the cubic protein microcrystals continuously releasing each factor for more than 1 month (13,14,15). Fgf2 and Lif were successfully enriched in the surrounding areas of each polyhedra where Erk also appeared to be hyperphosphorylated ( Supplementary Fig.…”
Section: Fgf2 Inhibits Osteogenesis In a Human Osteosarcoma Cell Linementioning
confidence: 98%
See 1 more Smart Citation
“…Collectively, Fgf2 suppressed the osteogenic process in AX cells at the mRNA level and the mechanism might be dependent on the hyperactivation of Erk1/2. To further evaluate the earlier findings in vivo, AX cells were coinjected with Fgf2 or Lif polyhedra which were the cubic protein microcrystals continuously releasing each factor for more than 1 month (13,14,15). Fgf2 and Lif were successfully enriched in the surrounding areas of each polyhedra where Erk also appeared to be hyperphosphorylated ( Supplementary Fig.…”
Section: Fgf2 Inhibits Osteogenesis In a Human Osteosarcoma Cell Linementioning
confidence: 98%
“…To overexpress Fgf2 and Lif in tumors in vivo, 2 million AX cells were mixed with Fgf2 polyhedra (125 ng of Fgf2 per an injection; refs. 13,14) or Lif polyhedra (25 ng of Lif per an injection; ref. 15) suspended in PBS containing 50 ng/mL Fgf2 or 1,000 U/mL Lif, respectively and subcutaneously injected.…”
Section: Tumor Xenograft Modelmentioning
confidence: 99%
“…Indeed, this sequestration can be essential to their function, as with fibroblast growth factor-2 (FGF-2). 22 Consequently, their activity in vivo reflects a delicate balance between free and bound forms.) The ECM can be subdivided into fibrous proteins, nonfibrous molecules, and enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to making up the turret/B-spike, VP4, and specifically its N-terminal segment (residues 1 to 79), was shown to "immobilize" foreign proteins onto the polyhedron (8,9), suggesting it may bind polyhedrin within polyhedra. A follow-up biochemical study further suggested the existence of a "polyhedrin recognition signal" within amino acid residues 42 to 93 that is sufficient to immobilize foreign proteins tagged by this fragment (7,13). We took note of the fact that some proteins failed to be immobilized (9), suggesting that there could be alternative interpretations for the immobilization.…”
mentioning
confidence: 89%